2015
DOI: 10.1007/s12010-015-1644-9
|View full text |Cite
|
Sign up to set email alerts
|

Indigoids Biosynthesis from Indole by Two Phenol-Degrading Strains, Pseudomonas sp. PI1 and Acinetobacter sp. PI2

Abstract: In this study, two phenol-degrading bacterial strains, designated as PI1 and PI2, were isolated from activated sludge for the production of indigoids from indole. According to the 16S ribosomal RNA (rRNA) gene sequence analysis, strains PI1 and PI2 were identified as Pseudomonas sp. and Acinetobacter sp., respectively. Liquid chromatography/time-of-flight/mass spectrometry (LC/TOF/MS) was applied to analyze the metabolites during the biotransformation of indole by the phenol-degrading strains. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…sp. QM and PI1 could also produce indigo, and other red and purple indigoids were also generated (Ma et al, 2012 ; Wang et al, 2015 ).…”
Section: Indole To Indigo: a Subject Of Unfailing Interestmentioning
confidence: 99%
“…sp. QM and PI1 could also produce indigo, and other red and purple indigoids were also generated (Ma et al, 2012 ; Wang et al, 2015 ).…”
Section: Indole To Indigo: a Subject Of Unfailing Interestmentioning
confidence: 99%
“…Pseudomonas sp. PI1 can cometabolize indole in the presence of phenol but cannot use indole as the sole carbon source ( 9 ). Application of liquid-chromatography time-of-flight mass spectrometry revealed four products with an m/z of 262.067, all of which had the same molecular formula with indigo, i.e., C 16 H 10 N 2 O 2 .…”
Section: Genome Announcementmentioning
confidence: 99%
“…PI1 and Acinetobacter sp. PI2 isolated from activated sludge could biosynthesis indigo [32]. Qu et al [33] reported transformation of indole to indigo using a biphenyl dioxygenase enzyme cloned from Dyella ginsengisoli L-4 and heterologously expressed in Escherichia coli (DE3).…”
Section: Introductionmentioning
confidence: 99%